2020
DOI: 10.1007/s11252-020-01062-7
|View full text |Cite
|
Sign up to set email alerts
|

Green infrastructures and ecological corridors shape avian biodiversity in a small French city

Abstract: In the context of increasing urbanization, preserving urban biodiversity has become a priority because biodiversity appears to be a key element when evaluating the well-being of urban residents. Recently, urban management has relied on a 'renaturing' strategy to improve biodiversity, but the benefits of these policies remain debated. In this study, we evaluated the effects of urban land use and green corridors on (1) urban avian biodiversity, and (2) the presence of the most common (top 70%) and least common (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 102 publications
(143 reference statements)
1
12
0
Order By: Relevance
“…While urban built form variables were important in improving the performance of several models, patch size was the strongest predictor and was present in each of the best models across all groups. Ultimately this study confirms previous assertions that the size of the UGS is the strongest predictor (Ikin et al, 2013;Strohback et al, 2013;Beninde et al, 2015;Dale, 2018;Amaya-Espinel et al, 2019;Beaugeard et al, 2020;Lynch, 2019;La Sorte et al, 2020). This finding supports the well-established species-area relationship (Lomolino, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…While urban built form variables were important in improving the performance of several models, patch size was the strongest predictor and was present in each of the best models across all groups. Ultimately this study confirms previous assertions that the size of the UGS is the strongest predictor (Ikin et al, 2013;Strohback et al, 2013;Beninde et al, 2015;Dale, 2018;Amaya-Espinel et al, 2019;Beaugeard et al, 2020;Lynch, 2019;La Sorte et al, 2020). This finding supports the well-established species-area relationship (Lomolino, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…The ecological functions of water ecological corridors include purifying water bodies and protecting soil [39]. The green space ecological corridors were mainly located in forest and green areas, which can accelerate the rate of material and energy exchange between ecological source sites [40]. One road type ecological corridor was identified along the coastal line in the south of Qingdao.…”
Section: Construction Of Ecological Corridorsmentioning
confidence: 99%
“…GI plays a big role in providing such habitats in urban areas (Ferenc et al, 2014;Filazzola, Shrestha, MacIvor, 2019) A study by Sweet and colleagues, using data from Global Biodiversity Information Facility (GBIF), concluded that selected German cities from all states foster a considerable percentage (76%) of local biodiversity (Sweet et al, 2022). However, nature can thrive and thus provide us with valuable ecosystem services if certain habitat conditions are met (Beaugeard et al, 2020;Angold et al, 2006;Rudd et al, 2002). A study by Beaugeard et al found that local urban biodiversity richness is highly bene ted from the presence of green areas, proximity to the edge of the urban centre, and the proximity to green corridors.…”
Section: Introductionmentioning
confidence: 99%